Revisions to geological unit names in New Brunswick, Canada, to address culturally offensive or inappropriate nomenclature - Dahn, Dustin R.L.; Smith, Erin A.; Pagé, Philippe (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
Recent amendments to the North American Stratigraphic Code enable the renaming of offensive or inappropriate unit names. Although the Province of New Brunswick has commenced the identification and renaming of culturally inappropriate geographic features, the use of offensive toponyms presents a problem in the naming of geological units. Names of eight geological units and structures in New Brunswick are culturally inappropriate or offensive. Following the guidelines in the amended Stratigraphic Code, replacement names for these problematic units and structures are proposed herein.